Effect of probiotic supplementation on growth performance of Osmanabadi kids - SIDDIQUI, M B A; PAWAR, N B; KHARWADKAR, M D; ALI, S SAJID; MUNDE, V K; WANKAR, A K (The Indian Journal of Animal Sciences, 2022)
The present experiment was conducted for 90 days to assess the effect of probiotic supplementation on performance of Osmanabadi kids at Osmanabadi goat unit of Red Kandhari Research and Instructional Farm, College of Veterinary and Animal Sciences, MAFSU, Parbhani, Maharashtra. Eighteen male or female kids of 3-6 months age were selected and randomly divided on equal weight basis into three treatment groups viz. T0 (control) with basal ration, T1 group with basal ration plus probiotics (Aspergillus oryzae and Lactobacillus), T2 group with basal ration plus probiotics (Saccharomyces cerevisiae and Lactobacillus). The averages for weekly body weight (kg) of kids in different treatment groups (T0, T1 and T2) at the end of experiment were 12.69±0.27, 13.78±0.48, 14.94±0.34 kg, respectively. The weekly body weight gain was 0.35±0.01, 0.50±0.01, 0.58±0.01 kg, respectively while the average daily gain was 50.33±1.45, 70.83±0.70, 83.33±1.65 g, respectively, for T0, T1 and T2 groups. At the end of 13th week, FCR for T2 group was significantly lower (6.14±0.01) as compared to T1 (7.14±0.04) and T0 (9.20±0.28) groups. Highly significant differences were observed for weekly body weight, weekly body weight gain, average daily gain, weekly and daily feed intake. It can be concluded that Saccharomyces cerevisiae and Lactobacillus supplemented group (T2) exhibited better performance in terms of growth and FCR as compared to Aspergillus oryzae and Lactobacillus supplemented group (T1) and control (T0).